Community health worker team integration in Medicaid managed care: Insights from a national study - Wennerstrom, Ashley; Haywood, Catherine G.; Smith, Denise O.; Jindal, Dakshu; Rush, Carl; Wilkinson, Geoffrey W. (Frontiers in Public Health, 2023)
Introduction Community health workers (CHWs) have historically worked in community-based settings. Medicaid managed care organizations (MCOs) are integrating CHWs into their teams, largely to support social determinants of health. Little is known about how teams are structured in these environments or how CHWs and their supervisors perceive CHW roles in MCOs. Methods In 2021, two CHW professional associations and a university partnered to conduct a national cross-sectional survey of CHWs working with MCOs. Results A total of 146 CHWs representing 29 states and 55 supervisors working in 34 states completed the survey. Although two-thirds of supervisors said only a high school diploma or equivalent was required for hiring, over half of CHWs reported having a bachelors or graduate degree. The majority of CHWs (72.6%) and employers (80%) said CHWs receive training in core competencies. Under half of CHWs reported working with a registered nurse (RN) (45.8%) or social worker (43.8%), and about a third work with a behavioral health (36.3%) or primary care provider (33.6%). Among supervisors, 70.9% identified social workers as CHWs' team members and over half indicated CHW work with RNs (56.4%), behavioral health (54.5%) and primary care providers (52.7%). Over half of CHWs (52.1%) and roughly two thirds (63.6%) of supervisors indicated that CHWs use electronic health records. Roughly 85% of CHWs make referrals and roughly three quarters conduct social screenings. Around half of CHWs said they assist with care planning (54.1%), conduct health screenings (52.1%) or participate in case reviews (49.3%). About three quarters of CHWs (75.3%) and over two thirds of supervisors (67.3%) believed that CHWs are utilized to their full potential. Under three quarters of CHWs (72.6%) and over half of supervisors (54.4%) believe CHWs are equitably compensated for their work. Discussion Overall, CHWs roles in MCOs appear to focus on supporting clinical care and making referrals for social issues, rather than addressing community-level concerns. Health plans should ensure that CHWs have the professional freedom to develop community-based solutions to common social needs. MCOs should also ensure that CHWs receive equitable compensation and ensure that CHWs have opportunities for promotion.